Striving for Energy Security: South Korea's Internal and External Energy Policy After the Fukushima Tragedy - Putri, Ardila; Lili Natalia, Vini (Indonesian Journal of Energy, 2023)
This paper analyzes South Korea's energy policy after the Fukushima disaster. The policy is seen from two dimensions, namely internal policies and external policies. The variable used in viewing the policy is through the framework described by Duffield. According to Duffield, internal policy responses can be seen from emergency preparations and reducing dependencies on foreign energy sources. In contrast, external policy response can be seen through policy toward energy-producing and transit countries, also other energy-consuming and importing countries. This research is qualitative with descriptive analytics. The study found that South Korea took several energy policies related to its domestic politics to reduce its dependence on energy imports. At the same time, for the external responses, South Korea intends to diversify its cooperation with the energy-exporting countries and continues to encourage international cooperation among the importing countries.